The determinants of high-performing sales leaders of MLM organizations in Malaysia: study from direct downlines' perspectives - Loo, Yew Liang (2020)
Multi-Level Marketing (MLM) is one of the marketing strategy to market products or services in domestic and international markets. Multi-Level Marketing Organizations (MLMO) have existed for decades. They develop and manage their sales forces by recruiting and motivating independent distributors to promote and sell products. MLMO also utilize the reward schemes to encourage recruitment of more distributors by the existing sales forces. In Malaysia, MLMO able to sustain their performance and progressing steadily even during the current economic uncertainty. However, the MLM industry is getting more competitive where competitors came out with variety business strategies, which made the conventional business tools practiced by MLMO have lost its effectiveness gradually. Thus, there is an increase in emphasis on highperforming sales leaders as key players to bring MLMO towards higher performance level, rather than just depending on classic MLM marketing tools which is by recruiting more downlines. As such, MLMO need to identify the determinants of highperforming sales leaders in order to improve their channel performance. This study therefore examined the relationships between transformational leadership, entrepreneurial orientation, relationship marketing and channel performance. It also examined the role of soft skills training program as a moderating variable between transformational leadership, entrepreneurial orientation, relationship marketing and channel performance. A survey was conducted among 320 respondents from 64 MLMO registered with Direct Sales Association of Malaysia (DSAM). Data was analysed using Statistical Package for Social Science (SPSS) software. The analyses revealed significant relationships between transformational leadership, entrepreneurial orientation, relationship marketing and channel performance. In addition, soft skills training program was found to moderate the relationship between transformational leadership, entrepreneurial orientation, relationship marketing and channel performance. Consequently, this study offers several implications especially on how MLMO can identify and positioned high-performing MLM sales leaders as a key player to lead their downlines towards achieving an optimum channel performance. Future studies may expand this study either by studying different independent variables, or to include mediating variable, or testing different type of respondents for different perspectives on high-performing sales leaders.